Routine use of ultrasound guided tandem placement in intracavitary brachytherapy for the treatment of cervical cancer – a South Indian institutional experience - Rao, Pamidimukkala Bramhananda; Ghosh, Saptarshi (Journal of Contemporary Brachytherapy, 2015)
Purpose: Intracavitary brachytherapy necessitates the insertion of a tandem applicator through the cervical os into the uterine cavity. Blind insertion of the tandem may result in suboptimal tandem placement. This decreases the control of the tumor locally and may result in uterine perforation. Although routine real time ultrasound guided tandem placement has shown better results, it is seldom practised. The aim of this work is to evaluate the role of routine real-time intraoperative trans-abdominal ultrasound guided tandem placement in intracavitary brachytherapy for the treatment of cervical cancer. Material and methods: This is a prospective single institutional study conducted from April 2013 to May 2015. A total of 96 patients of locally advanced cervical cancer were treated with routine ultrasound guided brachytherapy amounting to a total of 282 intracavitary applications. Results : In 78 of the study patients, the cervical os could be easily identified visually, which was then confirmed with ultrasound guidance. In another 12 patients, though the os could be identified visually, uterine sounding was only possible under ultrasound guidance. In another 4 patients, the cervical os could not be identified visually as the cervix was flushed with vagina and ultrasound guidance was necessary for accurate os identification. In 2 of the study patients, intraoperative ultrasound helped in identifying the patients suitable for interstitial brachytherapy rather than intracavitary brachytherapy. Out of the 96 study patients, the length of the uterine canal changed in 15 patients during the subsequent brachytherapy application. Conclusions : This procedure is strongly advocated for proper placement of the tandem applicator and to avoid perforations. It is an accurate, fast, easily available, and cost-effective method. Hence, it can be incorporated in intracavitary applications for cervical cancers even in the developing countries where cost, accessibility, and time are important issues.